The Association of Pistia stratiotes and Fish in the Dam of the Fisheries and Marine Science Faculty, Riau University - Cyntia Uli Artha Sihombing; Efawani '; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The water surface of the dam of the Fisheries and Marine Science Faculty of Riau University is almost covered by Pistia stratiotes and this condition may affect the availability of fish in that area. To understand the types of fish associated with that aquatic plant, a research has been conducted February to March 2017. Based on plant density, there were 3 sampling sites, site 1 (46.19 plants/m2), site 2 (14.6 plants/m2) and site 3 (52.31 plants/m2). A modified quadrant (2 x 2 m, completed with fish trapping net attached) was placed for an hour in each site. Samplings were conducted 4 times, once/week. Results shown that there is a relationship between the plant density and the number of fish as well as the types of fish present. As the density of the plant increase, the number and type of fish present was also increase. The types of fish present are as follows: Trichogaster trichopterus, T. pectoralis, Trichopsis vittata, Rasbora einthovenii, Oreochromis nilloticus, Xenentodon canciloides, and Channa striata. In the lower surface of the plant, there were fish eggs attached. Data obtained indicate that there were 7 fish species associated with P. stratiotes and the community of the plant may serves as hatchery of the associated fish.Keywords : The Dam of the Fisheries and Marine Science Faculty of Riau University, Aasosoation